(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article theoretically substantiates the fact that proverbs are linguistic units that provide a vivid picture of a nation’s culture, lifestyle, traditions, worldview, and spirituality, and that folk proverbs, a type of figurative language widely used to express wisdom, advice, and cultural values, reflect the language and cultural characteristics of a particular nation.